Joint longitudinal trajectories of pain intensity and opioid prescription in veterans with back pain. Issue 12 (27th September 2022) - Buta, Eugenia; Gordon, Kirsha S.; Gueorguieva, Ralitza; Becker, William C.; Heapy, Alicia; Bathulapalli, Harini; Zeng, Qing; Redd, Doug; Brandt, Cynthia; Goulet, Joseph
Abstract: Purpose: We describe pain intensity and opioid prescription jointly over time in Veterans with back pain to better understand their relationship. Methods: We performed a retrospective cohort study on electronic health record data from 117 126 Veterans (mean age 49.2 years) diagnosed with back pain in 2015. We used latent class growth analysis to jointly model pain intensity (0–10 scores) and opioid prescriptions over 2 years to identify classes of individuals similar in their trajectory of pain and opioid over time. Multivariable multinomial logit models assessed sociodemographic and clinical predictors of class membership. Results: We identified six trajectory classes: a "no pain/no opioid" class (22.2%), a "mild pain/no opioid" class (45.0%), a "moderate pain/no opioid" class (24.6%), a "moderate, decreasing pain/decreasing opioid" class (3.3%), a "moderate pain/high opioid" class (2.6%), and a "moderate, increasing pain/increasing opioid" class (2.3%). Among those in moderate pain classes, being white (vs. non‐white) and older were associated with higher odds of being prescribed opioids. Veterans with mental health diagnoses had increased odds of being in the painful classes versus "no pain/no opioid" class. Conclusion: We found distinct patterns in the long‐term joint course of pain and opioid prescription in Veterans with back pain. Understanding these patterns and associated predictors may help with development of targeted interventions for patients with back pain.